Organisational Communication And Employee Engagement In Hotels (PUSA Journal of Hospitality and Applied Sciences, 2018)
Background: Organizations have increasingly come to recognise the importance of employee  engagement over recent years. Employers are increasingly aware of the importance of engagement  for organisational success, and the need to measure engagement and to take steps to improve it. One  of the simple ways to increase the engagement is through an effective day-to-day communication  process. Internal communication helps in the building high transparency level among managers  and employees thus leading to a high engagement. There is no direct linkage at the organization  level between engagement and communication. Due to lack of integration many time employee  engagement programmes are not successful. Therefore a systematic study of communication  and engagement is needed. Objective: To understand the impact and relation of organizational  communication and employee engagement. Methodology: Quantitative research design was used  and data was collected by questionnaire technique. The sample comprised of 50 respondents including  associates, supervisors and managers of WelcomHotelDwarka, New Delhi. The attitude was assessed  using five point Likert Scale questionnaire of EES Gallup and Institute for Employment Studies. Results: Communication is highly and positively related with engagement level of the employees.  Open Communication leads to high employee suggestion involvement; they feel valued which directly  affect the employee engagement. Conclusion: Employee communication is directly proportional  to employee engagement. Open communication brings a degree of fairness and transparency lead  to engaged employees. High engaged employees receive communication more frequently than low  engaged employees. Employer has an understanding for the employees’ expectation and future plans
Keywords: Employee Engagement; Communication; Hotels